Funtional Ecology of fronds in Iberian saxicolous ferns - Seral Puyoles, Andrea; Murciano Cespedosa, Antonio; Molino de Miguel, Sonia; de la Fuente Brun, Pablo; Gabriel y Galán, Jose María (Acta Botanica Malacitana, 2018)
Nowadays, functional traits are widely used to study autoecological aspects in plant species. The analysis of these traits among climatic gradients allows us to know the strategy that plants follow depending on resource availability. Referring to plants, the traits measured in the leaves have a special importance; among these traits we can find SLA (Specific Leaf Area), LDMC (Leaf Dry- Matter Content) and LT (Leaf Thickness). In this work, these traits are measured in four species of the genus Asplenium. As extremes of a climatic gradient, we have focused our study in both bioclimatic regions existing in the Iberian Peninsula. Taking into account the differences referring to the resource availability for the species in each region, the main goal of this work is analyzing the variations of the three functional traits mentioned in the four species in both locations and associate these variations to macroclimatic variables. To this aim, fronds from the four species were collected in populations of each bioclimatic region to determine the fresh weight, dry weight and the foliar area. From these variables, we calculated the three functional traits. The results have shown that ferns adopt higher productive yields in the Mediterranean region (higher SLA values) and lower LDMC and LT values than in the Eurosiberian region. As to the climate variables effects, the average of the maximum temperatures in the warmest month (TMAX) is the variable that better explains the differences in the productive yield that the plants adopt in each region. On the other hand, annual precipitation seems not to play an important role on any of the functional traits in any of the species. Finally, we didn’t find a generalized tendency in the effects of the extern variables: frozen period, minimum temperatures in the coolest month and arid period.